Relationship between the roots of Hippophae rhamnoides at different stump heights and the root microenvironment in feldspathic sandstone areas - Liu,Lu; Guo,Yuefeng; Liu,Xiaoyu; Yao,Yunfeng; Qi,Wei (PeerJ, 2023)
Background To solve the withering of Hippophae rhamnoides plantation in the feldspathic sandstone areas of Inner Mongolia and to promote the regeneration, rejuvenation, and sustainability of H. rhamnoides forests. Methods We stumped aging H. rhamnoides trees at the ground heights of 0, 10, 15, and 20 cm (S1, S2, S3, and S4, respectively) and utilized unstumped trees as the control (CK). We then analyzed the effects of the different stump heights on the roots and the root microenvironment of H. rhamnoides and the relationship between the roots and the root microenvironment in the stumped H. rhamnoides. Results The root fractal features, root branching rate, root length, root soluble proteins, soil moisture content, and soil nutrients among the different treatments were ranked as S3>S2>S1>S4>CK (P < 0.05). The root topological index, root proline, and malondialdehyde among the different treatments were ranked as S3<S2<S1<S4<CK (P < 0.05). The topological indices of S1, S2, S3, S4, and CK were 0.80, 0.86, 0.89, 0.94, and 0.98, respectively, and all were near 1. This result indicated a typical fishtail-shaped branching structure. The root length and root fractal dimensions were primarily affected by the positive correlation of the soil moisture content and the soil organic matter, and the root topological index was primarily affected by the negative correlation of the root proline. Root nutrients were dominant in the changes in the root architecture, while soil moisture and nutrients played supporting roles. These results indicated that stumping can promote plant root growth and root nutrient accumulation, thereby improving soil moisture and the soil nutrient distribution, and the S3 treatment had the greatest impact on the H. rhamnoides roots and root microenvironment. Therefore, the 15 cm stump height treatment should be implemented for withering H. rhamnoides in feldspathic sandstone areas to promote vegetation restoration.
Keywords: Feldspathic sandstone areas; Vegetation restoration; Hippophae rhamnoides root; Root microenvironment; Stump height